2013
DOI: 10.1200/jco.2013.31.15_suppl.3086
|View full text |Cite
|
Sign up to set email alerts
|

Active immunotherapy in patients with progressive disease (PD) after first-line therapy: Racotumomab experience.

Abstract: 3086 Background: Racotumomab is a therapeutic vaccine that induces a cellular and humoral immune response against NeuGc-containing gangliosides expressed in several tumors but not in normal human tissues. A previous randomized, double blinded, placebo-controlled trial has demonstrated low toxicity of racotumomab and a statistically significant benefit in overall survival (OS) in patients with advanced non-small-cell lung cancer (NSCLC) who had achieved partial or complete response or disease stabilization aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is a tumor that responds poorly to chemotherapy and for which the treatment of choice is surgery (not applicable to these patients for various reasons). [29,31] Clinical studies [31,[32][33][34] have shown that the racotumomab vaccine increases survival in patients with recurrent or advanced stage (IIIB/IV) non-small cell lung cancer, compared to patients treated with best-practice supportive care. The vast majority in our research (70/71; 98.6%) completed the induction phase (the fi rst four cycles of the vaccine), the completion of which results in a better immune response.…”
Section: Original Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a tumor that responds poorly to chemotherapy and for which the treatment of choice is surgery (not applicable to these patients for various reasons). [29,31] Clinical studies [31,[32][33][34] have shown that the racotumomab vaccine increases survival in patients with recurrent or advanced stage (IIIB/IV) non-small cell lung cancer, compared to patients treated with best-practice supportive care. The vast majority in our research (70/71; 98.6%) completed the induction phase (the fi rst four cycles of the vaccine), the completion of which results in a better immune response.…”
Section: Original Researchmentioning
confidence: 99%
“…The overall survival rate at 5 years in patients with non-small cell carcinoma in the United States is 18%, [4] 9%-13% with a median survival of 9-12 months, and 30%-40% at 2 years and 10% at 5 years in the European Cancer Registry in Spain. [37] Various studies [29,32,34] have shown that the racotumomab vaccine increases survival in patients with recurrent or advanced stage (IIIB/IV) non-small cell lung carcinoma compared with patients treated with best-practices supportive care. The fi rst study with racotumomab in patients with stage IIIB and stage IV non-small cell carcinoma reported median overall survival of 16.4 months from time of diagnosis and a median survival of 9.93 months from time of vaccination, for a 1-year survival rate of 34%.…”
Section: Survivalmentioning
confidence: 99%
See 1 more Smart Citation